Peran Literasi Keuangan Islam Dan Inovasi Pengguna Dalam Meningkatkan Adopsi Fintech Serta Kinerja UMKM Di Kecamatan Matesih - Kolefiyan, Ihsyan; Erwinda Sam Anafih (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2023)
UMKMs in Matesih Sub-district face challenges in financial management, especially in adopting financial technology (fintech) that can improve their performance. This study aims to provide the impact of Islamic financial literacy and user innovation on fintech adoption and MSME performance in the area. The method used is a survey with purposive sampling of MSME players who have used fintech for at least one year. Data were collected through questionnaires distributed online and analyzed using Smart PLS. The results show that Islamic financial literacy has a positive effect on user innovation, which in turn increases fintech adoption. In addition, fintech adoption is shown to improve MSME performance. These findings illustrate that improving financial literacy and user innovativeness can be an effective strategy to promote MSME growth in Matesih Sub-district